Effectiveness of the mild alkali and dilute polymer modification in controlling the durability of jute fibre in alkaline cement medium. (20th June 2018) - Kundu, Sarada Prasad; Chakraborty, Sumit; Majumder, Subhasish Basu; Adhikari, Basudam
Graphical abstract: Highlights: Effective modification of jute fibre using mild alkali and polymer emulsion. Evaluation of the durability performances of modified jute fibre in cement medium. Prediction of normalized tensile strength of jute fibre exposed to alkaline medium. Prediction of jute fibre mineralization using analytical techniques. Design of a model to explain durability performances of jute fibre. Abstract: With the aim to improve the durability of natural fibres used as fibre reinforcement in the cement matrix, the combined alkali and polymer modification would be a unique approach. The present investigation deals with the durability performances of the unmodified and combined mild alkali and polymer emulsion modified jute fibres exposed to alkaline medium and cement medium as well. Initially, the jute fibres were modified using mild alkali (0.5% NaOH, 24 h) and dilute polymer emulsion (0.125% carboxylated styrene butadiene rubber (SBR)) sequentially. Afterward, the unmodified and modified jute fibres were then exposed to the saturated lime solution, 0.1 N NaOH solution, and cement paste for 360 days. After periodic exposure in different media, the fibres were removed and tested. Based on the results, it is demonstrated that the combined alkali and polymer modified jute fibre retains 17, 19 and 20% more tensile strength as compared to that of the raw jute fibre after 360 days exposure in saturated lime solution, NaOH solution, and cement paste, respectively. The improved durability of the combined alkali and polymer modified jute appears to be due to the reduction of fibre mineralization by forming a protective coating of polymer on the fibre surface as demonstrated by elemental analysis, FTIR, XRD, NMR, SEM in conjugation with EDS.